Evolutionary trends in animal ribosomal DNA loci: introduction to a new online database - Sochorová, Jana; Garcia, Sònia; Gálvez, Francisco; Symonová, Radka; Kovařík, Aleš (Chromosoma, 2018)
Ribosomal DNA (rDNA) loci encoding 5S and 45S (18S-5.8S-28S) rRNAs are important components of eukaryotic chromosomes. Here, we set up the animal rDNA database containing cytogenetic information about these loci in 1343 animal species (264 families) collected from 542 publications. The data are based on in situ hybridisation studies (both radioactive and fluorescent) carried out in major groups of vertebrates (fish, reptiles, amphibians, birds, and mammals) and invertebrates (mostly insects and mollusks). The database is accessible online at www.animalrdnadatabase.com . The median number of 45S and 5S sites was close to two per diploid chromosome set for both rDNAs despite large variation (1-74 for 5S and 1-54 for 45S sites). No significant correlation between the number of 5S and 45S rDNA loci was observed, suggesting that their distribution and amplification across the chromosomes follow independent evolutionary trajectories. Each group, irrespective of taxonomic classification, contained rDNA sites at any chromosome location. However, the distal and pericentromeric positions were the most prevalent (> 75% karyotypes) for 45S loci, while the position of 5S loci was more variable. We also examined potential relationships between molecular attributes of rDNA (homogenisation and expression) and cytogenetic parameters such as rDNA positions, chromosome number, and morphology.
Keywords: Evolution, Molecular; Databases, Genetic; molekulární evoluce; karyotyp; ribozomální DNA; Chromosomes; Quantitative Trait Loci; Animals; internet; Web Browser; Internet; Karyotype; DNA, Ribosomal; databáze genetické; zvířata; lokus kvantitativního znaku; internetový prohlížeč; chromozomy